Maternal health situation in two states of central India: a comparative analysis - Soni, Vaishali (International Journal Of Community Medicine And Public Health, 2024)
The health of women during their pregnancies, deliveries, and postpartum periods is referred to as maternal health. Madhya Pradesh (MP) and Chhattisgarh (CG) are included in the National Rural Health Mission's "Empowered Action Group" states due to their poorer maternal health indicators. The main purpose of the study is to compare the "Maternal Health" indicators presented in the factsheets of the National Family Health Survey-4 and -5 for two major states of India: Chhattisgarh and Madhya Pradesh. The fact sheets of the National Family Health Survey for Madhya Pradesh and Chhattisgarh were obtained from reliable sources. The study compared the maternal health data extracted from the "NFHS-4" and "NFHS-5" fact sheets of these states to assess the state of maternal health. According to NFHS-5, it is evident that maternal health in the states of Chhattisgarh and Madhya Pradesh has not yet met the expected goals. However, when comparing NFHS-5 with NFHS-4, the maternal health indicators have shown improvement. The provision of antenatal care (ANC) is crucial for safe motherhood, and pregnant women are routinely given tetanus toxoid (TT) vaccinations and iron-folic acid (IFA) pills as part of comprehensive maternal care. Institutional care is essential to ensure that mothers remain healthy and survive childbirth. Despite these efforts, neither state has performed well in neonatal care during the first two days after birth. Compared to Madhya Pradesh's performance, Chhattisgarh's performance is relatively better. Action is needed to address the increasing number of caesarean section deliveries in private hospitals. The study presents the maternal health indicators for two major states of India. The data indicates that immediate improvements are necessary to enhance maternal health services in India.